Attaining SDG 2 (Zero Hunger) in Nigeria: The Role of the Plant Variety Protection Act 2021 - Ogunyemi, Jesuye John; Olubiyi, Ifeoluwa Ayokunle (ABUAD Law Journal, 2023)
The achievement of Zero Hunger by 2030 is the focus of the United Nation’s Sustainable Development Goal (SDG) 2. Despite its status as a major agricultural producer, Nigeria is confronted with a number of challenges that contribute to food insecurity and widespread hunger. The Plant Variety Protection Act 2021 was signed into law in Nigeria in 2021 to promote increased staple crop productivity for Nigerian smallholder farmers and to encourage investment in plant breeding and crop variety, as well as protect new plant varieties. This paper investigates the role of Nigeria’s Plant Variety Protection Act 2021 (PVPA) in achieving sustainable food security under SDG2. The Act, which was passed to promote the protection of plant varieties and breeders’ rights, has the potential to make a significant contribution to Nigeria’s food security and agricultural sustainability. The challenges and criticisms of the PVPA are also discussed, and solutions to help achieve the target of zero hunger by 2030 are suggested.